The beneficial effect of enhanced physical activity on the welfare of breast cancer survivors. (July 2014) - Allen, Summer VS; Hurley, Rachel M; Patel, Alpa V; Cheville, Andrea L; Pruthi, Sandhya
SUMMARY : Healthcare providers caring for breast cancer survivors can positively impact patients' quality of life by counseling them about lifestyle modifications such as physical activity and exercise. Based on a literature review of current available evidence, this article serves as a guide to primary care providers regarding the beneficial role of lifestyle modification and physical activity. Specific survivorship issues and beneficial impacts of physical activity that will be discussed in this article include the management of arthralgias, cancer related fatigue, lymphedema, pain, mental health conditions, weight management and reducing breast cancer recurrence. The timing and intensity of physical activity needs to be individualized based on patient symptoms, comorbidities and personal preferences. The goals of physical activity options for breast cancer survivors are to aid in the management of treatment-related side effects, improve fitness and maintain a healthy lifestyle.